Spectrophotometric Determination of Amiodarone Hydrochloride in Pharmaceutical Preparations - Salh, D. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Amiodarone hydrochloride (AH) has been determined spectrophotometrically Using methyl orange (MO).  In our previous researches MO was used for determination of Mexiletine Hydrochloride [1]. The method based on complexation between MO and AH.  After shaking and diluting the complex solution with D.W, the pH was adjusted with NaOH and HCl to pH 3. The colored complex formed between AH and the reagent were transferred into separating funnels and extracted using 5.5ml CH2Cl2 and were shaken for (5 minutes).  The extracted organic layer was used for preparation of the calibration curves for spectrophotometric measurements of AH at 434nm.  The blanks were carried out in exactly the same way throughout the whole procedure.  Molar absorptivity (Îµ L.mol-1.cm-1), detection limit, limit of linearity (Âµg.ml-1) and r2 were, 5.74 *105, 0.04 and 0.982 for (AH-MO) respectively. The method was used with reasonable accuracy and precision for the determination of (AH) in synthetic samples of tablets, capsules and ampoules.